2022
DOI: 10.1098/rsta.2022.0006
|View full text |Cite|
|
Sign up to set email alerts
|

10 years of research on toughness enhancement of structural ceramics by graphene

Abstract: Over the past decade, a new family of ceramic matrix composites has been developed from the incorporation of homogeneously dispersed graphene-based fillers (graphene nanoplatelets/GNP, graphene oxide sheets/rGO or graphene nanoribbons/GNR) into the ceramic matrices. These composites have shown a significant increment of their fracture toughness accompanied by other electrical and thermal functionalities, which make them potentially attractive for a wide range of applications. Here, the main methods for testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…This phenomenon is primarily attributed to higher nanocarbon reinforcement within an elevated ceramic matrix, which results in agglomeration and the formation of pores in the ceramic structure . Moreover, greater reinforcement material can intensify the contact between graphitic carbon plates, creating pathways between weakly bonded planes and consequently contributing to the rapid propagation of cracks . The significant enhancement in fracture toughness can be attributed to the presence of ZIF-67-derived graphitic carbon within the composites, which serves as a pivotal agent for both crack deflection and crack bridging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is primarily attributed to higher nanocarbon reinforcement within an elevated ceramic matrix, which results in agglomeration and the formation of pores in the ceramic structure . Moreover, greater reinforcement material can intensify the contact between graphitic carbon plates, creating pathways between weakly bonded planes and consequently contributing to the rapid propagation of cracks . The significant enhancement in fracture toughness can be attributed to the presence of ZIF-67-derived graphitic carbon within the composites, which serves as a pivotal agent for both crack deflection and crack bridging.…”
Section: Resultsmentioning
confidence: 99%
“…50 Moreover, greater reinforcement material can intensify the contact between graphitic carbon plates, creating pathways between weakly bonded planes and consequently contributing to the rapid propagation of cracks. 55 The significant enhancement in fracture toughness can be attributed to the presence of ZIF-67-derived graphitic carbon within the composites, which serves as a pivotal agent for both crack deflection and crack bridging. Crack deflection describes the process by which a propagating crack tilts and twists, deviating from its original path as it encounters the reinforcing nanocarbon situated at the fragile interface formed with the matrix.…”
Section: Microstructure and Mechanicalmentioning
confidence: 99%
“…For example, nanocarbon derivatives such as graphene and carbon nanotubes tend to agglomerate due to their high surface area, surface energies, and van der Waals forces from intermolecular electrical dipoles, which degrade the mechanical properties of ceramic composites. 10,11 Therefore, it is difficult to disperse these materials homogeneously in a ceramic matrix. Several techniques and additional processes have been proposed to improve the dispersity of nanocarbons in a ceramic matrix, but this increases the complexity of their production and, therefore, increases the overall cost.…”
mentioning
confidence: 99%
“…To this end, carbon allotropes, such as graphite, carbon nanofiber, carbon nanotubes, and graphene, have been integrated into the ceramic matrix to increase the conductivity and mechanical strength of the ceramics. Although most of the studies have reported that the mechanical and electrical properties of ceramic composites reinforced with nanocarbon derivatives have been improved, there are still many challenges to overcome. For example, nanocarbon derivatives such as graphene and carbon nanotubes tend to agglomerate due to their high surface area, surface energies, and van der Waals forces from intermolecular electrical dipoles, which degrade the mechanical properties of ceramic composites. , Therefore, it is difficult to disperse these materials homogeneously in a ceramic matrix. Several techniques and additional processes have been proposed to improve the dispersity of nanocarbons in a ceramic matrix, but this increases the complexity of their production and, therefore, increases the overall cost .…”
mentioning
confidence: 99%
“…In the second group of papers [ 11 , 23 25 ], nanocracks in composite materials are emphasized, starting with carbon fibre-reinforced polymers [ 11 , 23 ], followed by a description [ 24 ] of ceramics toughened by graphene nanoparticles. Then, the interesting layered structure of slug-teeth is examined to show that nano-scale toughness can arise in nature [ 25 ].…”
mentioning
confidence: 99%